Blood-Brain Barrier Damage in Ischemic Stroke and Its Regulation by Endothelial Mechanotransduction - Nian, Keqing; Harding, Ian C.; Herman, Ira M.; Ebong, Eno E. (Frontiers in Physiology, 2020)
Ischemic stroke, a major cause of mortality in the United States, often contributes to disruption of the blood-brain barrier (BBB). The BBB along with its supportive cells, collectively referred to as the “neurovascular unit,” is the brain’s multicellular microvasculature that bi-directionally regulates the transport of blood, ions, oxygen, and cells from the circulation into the brain. It is thus vital for the maintenance of central nervous system homeostasis. BBB disruption, which is associated with the altered expression of tight junction proteins and BBB transporters, is believed to exacerbate brain injury caused by ischemic stroke and limits the therapeutic potential of current clinical therapies, such as recombinant tissue plasminogen activator. Accumulating evidence suggests that endothelial mechanobiology, the conversion of mechanical forces into biochemical signals, helps regulate function of the peripheral vasculature and may similarly maintain BBB integrity. For example, the endothelial glycocalyx (GCX), a glycoprotein-proteoglycan layer extending into the lumen of bloods vessel, is abundantly expressed on endothelial cells of the BBB and has been shown to regulate BBB permeability. In this review, we will focus on our understanding of the mechanisms underlying BBB damage after ischemic stroke, highlighting current and potential future novel pharmacological strategies for BBB protection and recovery. Finally, we will address the current knowledge of endothelial mechanotransduction in BBB maintenance, specifically focusing on a potential role of the endothelial GCX.